2004
DOI: 10.1530/rep.1.00241
|View full text |Cite
|
Sign up to set email alerts
|

Deadly decisions: the role of genes regulating programmed cell death in human preimplantation embryo development

Abstract: Human preimplantation embryo development is prone to high rates of early embryo wastage, particularly under current in vitro culture conditions. There are many possible underlying causes for embryo demise, including DNA damage, poor embryo metabolism and the effect of suboptimal culture media, all of which could result in an imbalance in gene expression and the failed execution of basic embryonic decisions. In view of the complex interactions involved in embryo development, a thorough understanding of these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 87 publications
2
82
1
3
Order By: Relevance
“…The variety of tools available for studying mouse genetics make the mouse well suited as a model system and more is likely known about gene regulation in the mouse than any other species. Consequently, the depth and breadth of information in this area are outside the scope of this brief review and the reader is referred to several recent reports [22][23][24][25][26] An area particularly relevant to the study of preimplantation embryo development is imprinting. Animals produced using ART may differ phenotypically from animals produced by natural mating.…”
Section: Use Of the Mouse To Understand Gene Function And Regulation mentioning
confidence: 99%
“…The variety of tools available for studying mouse genetics make the mouse well suited as a model system and more is likely known about gene regulation in the mouse than any other species. Consequently, the depth and breadth of information in this area are outside the scope of this brief review and the reader is referred to several recent reports [22][23][24][25][26] An area particularly relevant to the study of preimplantation embryo development is imprinting. Animals produced using ART may differ phenotypically from animals produced by natural mating.…”
Section: Use Of the Mouse To Understand Gene Function And Regulation mentioning
confidence: 99%
“…It is generally accepted that the oocyte is in control of early embryogenesis: during early cleavage stages, embryonic development is supported by maternal mRNAs and proteins synthesized and stored during oocyte growth (Fair et al 1995). Inadequate provision of maternal products to the early embryo may lead to delayed embryo development or even embryonic demise (Jurisicova & Acton 2004). Transcripts of genes of Bcl-2 family members are present at different levels in human oocytes, resulting in a different balance in expression of pro-and anti-apoptotic genes, which may shift the oocyte's developmental potential in the direction of either cell death or cell survival (Jurisicova & Acton 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate provision of maternal products to the early embryo may lead to delayed embryo development or even embryonic demise (Jurisicova & Acton 2004). Transcripts of genes of Bcl-2 family members are present at different levels in human oocytes, resulting in a different balance in expression of pro-and anti-apoptotic genes, which may shift the oocyte's developmental potential in the direction of either cell death or cell survival (Jurisicova & Acton 2004). We have recently shown that maternal transcripts of caspase-3 and -7, which play an important role in the caspase cascade of apoptosis, are also expressed in 40 and 30% of bovine oocytes respectively, but we could not demonstrate the presence of active caspases in fresh oocytes (Yuan et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that apoptosis allows the elimination of ICM cells that retain trophectodermal potential and contributes to the threshold number of ICM cells compatible with a correct development of the embryo (15,19,33). In E4.5 mNle Ϫ/Ϫ blastocysts, ICM cells were shown to degenerate through a caspase 3-dependent apoptotic process.…”
Section: Discussionmentioning
confidence: 99%